Essays in credence goods and repeated games - Bailey, K; Kirk James Bailey (2011)
This thesis presents two chapters on credence goods and one on ongoing partnerships in an infinitely repeated game. The chapters on credence goods focus on the welfare and efficiency of equilibria in overcharging models of credence goods, something which has not been explicitly addressed before. The chapter on partnerships presents a theory explaining ongoing partnerships as solving a commitment problem for clients. There is a small literature on partnerships, and this chapter represents a novel but complimentary approach to that literature. At core, chapters 2, 3 and 4 of this thesis ask the following questions respectively: Do competition and information increase welfare in credence goods markets? How do customers in credence goods markets discipline experts from committing fraud? Can these strategies be welfare ranked? Why do ongoing partnerships exist? What problem do they solve?